Economic page turners - Björn Frank (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
Economic page turners like Freakonomics are well written and there is much to be learned from them - not only about economics, but also about writing techniques. Their authors know how to build up suspense, i.e., they make readers want to know what comes. An uncountable number of pages in books and magazines are filled with advice on writing reportages or suspense novels. While many of the tips are specific to the respective genres, some carry over to economic page turners in an instructive way. After introducing some of these writing tools, I discuss whether these and other aspects of good writing lead to a biased presentation of economic theory and practice. I conclude that, whatever the problems with certain economic page turners may be, they are not due to the need to write in an accessible, appealing way.
Keywords: 330; Wirtschaftswissenschaft; Publikationsanalyse; Wissenschaftliches Arbeiten; Bias